Fuzzy Logic Based Motor Control - Mohamed Fayek, Haytham (Universiti Teknologi Petronas, 2011)
This report presents the detailed design of both Type-1 Fuzzy logic PI controller and Type-2 Fuzzy Logic PI controller to control the speed of a DC servomotor. Both controllers are explored extensively in terms of number and type of membership functions and the defuzzification technique used. Rise time, Settling time, Percent overshoot and Integral Absolute error are used to judge between controllers during a unity step response, load disturbance and noise disturbance. Using Simulink Matlab, simulation to show the behavior of the DC servomotor will be carried; to compare type-2 fuzzy logic against conventional type-1. Moreover, explain the advantages and disadvantages of fuzzy logic over conventional PID controllers. A DC servo motor model was built and the performance of a PID controlled system was simulated. Afterwards, type-1 fuzzy logic controller was simulated to determine the system performance. Moreover, both types of controllers were compared against each other to determine the advantages and disadvantages of both. Furthermore, type-1 fuzzy logic controller was explored further where judgment of the performance of the system was carried by varying the number of membership functions, type of membership functions and defuzzification methods. Afterwards, type-2 fuzzy logic controller was simulated and explored in the same manner as type- 1 fuzzy logic controller. Both controllers were compared to analyze the advantages and disadvantages of each. A comparative analysis with the conventional type-lfuzzy logic PI controller shows that overall, type-2 showed much improved results. This improvement is evident when it comes to handling ofload disturbance and noise added to the system.